2013
DOI: 10.2478/s11756-013-0168-4
|View full text |Cite
|
Sign up to set email alerts
|

Spruce monoculture establishment affects functional traits of soil microarthropod communities

Abstract: Structure and density of soil microarthropod communities (Oribatida and Collembola) were studied in one natural beech forest and one spruce monoculture planted on a former beech stand in South Bohemia (Czech Republic in the spruce monoculture for Collembola); additionally, it changed greatly the community structure in terms of species composition and functional traits. In the spruce monoculture, groups susceptible to disturbance were suppressed. The oribatid trophic structure changed as well with opportunistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…At the same experimental site, Rousseau et al (2018) found that springtail and oribatid mite species were more prevalent in the moss horizon than in mineral soil, possibly explaining their decreasing abundance with increasing soil exposure. Hemiedaphic springtails are mostly found in thick forest floors (Farská et al, 2013;Salmon et al, 2014) , 2006). Similarly, web builder spiders were less prevalent in disturbance treatments where sparse vegetation provide limited attachment points (Castro and Wise, 2009).…”
Section: Direct Effects Of Disturbance On Biodiversitymentioning
confidence: 99%
“…At the same experimental site, Rousseau et al (2018) found that springtail and oribatid mite species were more prevalent in the moss horizon than in mineral soil, possibly explaining their decreasing abundance with increasing soil exposure. Hemiedaphic springtails are mostly found in thick forest floors (Farská et al, 2013;Salmon et al, 2014) , 2006). Similarly, web builder spiders were less prevalent in disturbance treatments where sparse vegetation provide limited attachment points (Castro and Wise, 2009).…”
Section: Direct Effects Of Disturbance On Biodiversitymentioning
confidence: 99%